An investigation into English idioms relating to fruit with reference to the Vietnamese equivalents / Đặng Thị Thanh Hương; NHDKH Dr.Nguyen Thi Van Dong - Đặng, Thị Thanh Hương
Idioms are used regularly and naturally in everyday communication, however, the inner meaning of the concept of idioms is still unclear to a lot of people. Therefore, The author thinks a study on the subject of idioms in Vietnamese and English is helpful for improving the knowledge of language learners, as well as the students learning English in general. In the study the author finds out that a semantic and syntatic analysis of English and Vietnamese idioms relating to fruit has shown that English and Vietnamese idioms relating to fruit mention appearance, moods and feelings, love affairs and relationship, success or failure. Besides that the use of English and Vietnamese idioms can be explained behavior, attitude, activity and action, advantageous or disadvantageous situation, poverty, geography. Although I dioms are classified in different groups in which the author chooses symantic and syntactic of English idioms relating to fruit with reference to the Vietnamese equivalents to be my subjects as they occupy a significant role and have special structure, is an appropriate subject for a study contrastive. Besides that, the survey in the form of questionare carried out by 60 students in the First year studens at University of Economics and Technical Industries is to find out the comman mistakes in using Fruit idioms in English. Finally, some implications for teaching ans learning of English at University of Economics and Technical Industries were suggessted.